Observations of hyperluminous infrared galaxies with the Infrared Space Observatory: Implications for the origin of their extreme luminosities - Verma, A; Rowan-Robinson, M; McMahon, R; Efstathiou, A (2002)
We present 7-180 μm photometry of a sample of hyperluminous infrared galaxies (HyLIGs) obtained with the photometer and camera mounted on the Infrared Space Observatory. We have used radiative transfer models of obscured starbursts and dusty torii to model their spectral energy distributions (SEDs). We find that IRAS F00235+1024, IRAS F14218+3845 and IRAS F15307+3252 require a combination of starburst and active galactic nuclei (AGN) components to explain their mid-to far-infrared (FIR) emission, while for TXS 0052+471 a dust torus AGN model alone is sufficient. For IRAS F00235+1024 and IRAS F14218+3845 the starburst component is the predominant contributor, whereas for IRAS F15307+3252 the dust torus component dominates. The implied star formation rates (SFRs) for these three sources estimated from their infrared luminosities are M*,all > 3000 M⊙ yr-1 h-250 and are amongst the highest SFRs estimated to date. We also demonstrate that the well-known radio-FIR correlation extends into both higher radio and infrared power than previously investigated. The relation for HyLIGs has a mean q value of 1.94. The results of this study imply that better sampling of the infrared spectral energy distributions of HyLIGs may reveal that both AGN and starburst components are required to explain all the emission from the near-infrared to the submillimetre.